Sex and Marriage in Machiavelli’s Mandragola: A Close(t) Reading - Eisenbichler, Konrad (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
This article carries out a close reading of Niccolò Machiavelli’s play Mandragola (The mandrake root) from the perspective of sex and gender studies. In so doing, it takes into consideration what the play says or suggests about sexual desire, sexual practices, and conjugal life. This somewhat less conventional examination reveals that, under cover of entertainment and humour, Machiavelli was raising important questions about contemporary marriage conventions and sexual practices that ranged from the difference in age between the spouses to the difference in their sexual interests, from a couple’s desire for progeny to the partners’ (un)willingness to pay the marriage debt, from the matter of a man’s “honour” to the question of a woman’s “worth.”